Analisis Sistem Informasi Akuntansi Persediaan terhadap PDAM Tirtanadi Sumatera Utara - Sri Rahayu; Saparuddin Siregar (Universitas Muhammadiyah Enrekang, 2022)
The purpose of PDAM Tirtanadi is to manage and provide drinking water services that meet health requirements and to develop the regional economy, increase regional income, and improve environmental quality by providing services for collecting and distributing wastewater through a piping system in order to achieve public welfare in general.This study aims to determine how the inventory accounting information system at PDAM Tirtanadi North Sumatra. The analytical method used in this research is a descriptive method.The results of the study can be concluded that the inventory information system has a very important role in the company so as to get the desired results optimally without fraud.